Lee Bennett Hopkins a children's poet - Strong, Amy (New York Franklin Watts, 2003)
Looks at the life and work of children's poet Lee Bennett Hopkins, who has been a full-time writer for over twenty-five years
American Corner
Includes bibliographical references (p. [103]-105) and index
5 11
Keywords: Hopkins, Lee Bennett -- Juvenile literature; Poetry -- Authorship -- Juvenile literature; Poets, American -- 20th century -- Biography -- Juvenile literature